Bi-allelic missense ABCA3 mutations in a patient with childhood ILD who reached adulthood. Issue 3 (22nd July 2019) - Manali, Effrosyni D.; Legendre, Marie; Nathan, Nadia; Kannengiesser, Caroline; Coulomb-L'Hermine, Aurore; Tsiligiannis, Theofanis; Tomos, Pericles; Griese, Matthias; Borie, Raphael; Clement, Annick; Amselem, Serge; Crestani, Bruno; et al.
The adenosine triphosphate (ATP)-binding cassette subfamily A member 3 (ABCA3) is a transmembrane glycoprotein that uses energy of ATP hydrolysis to transport phospholipids into the lamellar bodies of type 2 alveolar epithelial cells (AEC) and regulates lung surfactant homeostasis. More than 200 mutations have already been described in ABCA3, located on chromosome 16 [1, 2]. Patients present with a great heterogeneity of phenotypes, from lethal neonatal respiratory distress syndrome (RDS) to childhood and rarely adult interstitial lung disease (ILD) [3, 4]. ABCA3 mutations-related lung disease inheritance is autosomal recessive, as it requires two disease-causing (bi-allelic) mutations, one from each parent. Children with ABCA3 mutations may survive beyond infancy and reach adulthood. Genetic mechanisms should always be examined in adult patients with childhood onset ILD and molecular analysis should be performed accordingly in specialised referral centres. http://bit.ly/2LzMNOE